Planning implications and sustainability of tourism: a comparative study of Hikkaduwa and Bentota, Sri Lanka / Medha Rasanjalee Gunawardana and H.L.G. Sanjeewani - Sanjeewani, H.L.G. (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2009)
Tourism is a multidimensional phenomenon and it has many activities in a community or region with ecological, economic, social and cultural effects which require planning and coordination. On the other hand, for effective sustainable tourism, careful planning, adaptation of the principles of sustainability and the implications of plans are required to gain maximum economic benefits and tourist satisfaction, while managing the natural resources of the destination. Systematically planned, equity-oriented tourism development may aid governments in building infrastructure, help the balance of payments, and generate foreign exchange which could be used to sustain the nation. The reality of the present situation is that in most developing countries’ tourism development often proceeds in an ad hoc way which is unreliable for the nation in search of quick and substantial economic gains. Hikkaduwa in Sri Lanka has undertaken ad hoc planning for tourism development. On the other hand the tourism industry in Bentota proceeded according to a tourism development plan. The question is the sustainability of the tourism industry in both destinations. This paper mainly focuses on evaluating the issues related to sustainability of tourism and planning implications and their effects on sustainable tourism development, using two case studies Hikkaduwa and Bentota. Tourism development in both tourist resorts is unsustainable in terms of the trio-fundamental requirements of sustainable tourism development. Comprehensive, flexible, community driven, sustainable and systematic planning approaches therefore need to be implemented to achieve sustainable tourism development